The Frequency of Axial Deposition in Korean Patients With Gout at a Tertiary Spine Center - Jin, Hyo-Joon; Son, Eun-Seok; Kim, Du Hwan (Frontiers in Medicine, 2020)
Objectives: This study aimed to describe the frequency of axial deposition (axial gout) and determine the associated factors in patients with gout who presented to a spine clinic in Korea. Methods: We enrolled 95 Korean patients who visited our spine center from March 2012 to February 2016 and who had been previously diagnosed with gout and had available computed tomography (CT) images of the vertebral columns. Axial gout was defined as the presence of erosions or tophi in the vertebral endplate or facet joint. Clinical and laboratory data of these patients were retrieved from medical records. Results: Out of the 95 patients, 15 (15.8%; 95% confidence interval [CI], 9.4-25.0%) had a conventional CT evidence suggestive of axial gout. In these 15 patients, 12 (80%) had lumbar spine involvement (95% CI, 51.4-94.7%). Fifteen patients had erosions of the vertebral columns, and two presented with tophi that exhibited erosive changes of the facet joints. Presence of axial gout was not associated with patients’ age, duration of gout, laboratory findings, inflammatory back pain symptoms, identification of monosodium urate crystals in the peripheral joints, current use of urate-lowering drugs, hypertension and end-stage renal disease; however, there was a significant association with the presence of diabetes (P=0.008). Conclusions: Frequency of axial deposition in Korean patients with gout and spinal symptoms was 15.8%, with the lumbar region being the most commonly involved section of the spine. In addition, diabetes was associated with evidence of axial gout on imaging.